Application of chitosan as sorbent of heavy metal ions - Kułak, Z.; Niekraszewicz, A.; Struszczyk, H. (Polimery, 2022)
The effects are studied of some basic physico-chemical parameters of chitosan (average molecular weight Mv, degree of deacetylation SD and water retention value MRV) on the sorption ability of chitosan and the beads produced on its base. Also the dependence between the chitosan beads sorption properties and the beads forming conditions (concentration of chitosan solution in hydrochloric acid and concentration of NaOH in coagulation bath) is characterized. Sorption of initial chitosan and the beads formed out of it is defined in relation to the chosen metal ions: Cu2+, Ni2+, Co2+, Cr6+. It has been found that sorption capacity and dynamics of sorption of chitosan beads is significantly higher than that of initial chitosan. Sorption properties of beads do not depend on the concentration of NaOH in coagulation bath (0.75-1.5 mass%) nor on the Mv of chitosan within the range of Mv (129-504) * 103 and SD (80-88%) (Tables 1 and 2). The ions Cu2+ sorbed best and Cr6+ ions worst - from the salts solutions examined.